Dicentrine is preferentially antagonistic to rat aortic than splenic alpha 1-adrenoceptor stimulation - Mustafa, Mohd Rais; Achike, F.I. (2000)
Dicentrine is a known a,-adrenoceptor antagonist,but its a,-adrenoceptor subtype selectivity has not yet been determined. We therefore, investigated the putative a, adrenoceptor subtype selectivity of this agent.